Analysis of Differences in Image Quality and Anatomical Information of Head CT Scan Examination in Non-Hemorrhagic Stroke Cases Using Sinogram Affirmed Iterative Reconstruction (SAFIRE) - Samudra, Alan; Fitriana, Lutfatul; Hidayat, Fathur Rachman; Wibowo, Kusnanto Mukti; Ariesma Githa Giovany; Caesarendra, Wahyu (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2025)
SAFIRE should be utilized to its full potential, as this innovative image reconstruction algorithm can significantly reduce image noise without loss of sharpness, preserving image quality and anatomical information. This is particularly important in the case of non-hemorrhagic stroke, where image noise can obscure small lesions, potentially leading to misdiagnosis and inappropriate treatment. SAFIRE has five variations of strength, making it essential to identify the most optimal SAFIRE Strength for head CT Scan examinations in non-hemorrhagic stroke cases. The aim of this study is to determine differences in image quality and anatomical information in head CT Scan of non-hemorrhagic stroke cases using SAFIRE variations to identify the most optimal SAFIRE Strength. This experimental quantitative study involved a sample of 30 patients, with each case reconstructed using five SAFIRE Strength variations. Image quality was assessed using the IndoQCT application, while anatomical information was evaluated through the visual grading analysis method by three radiologists. Image quality data were analyzed using the Friedman statistical test, which resulted in a p-value of 0.000 (p < 0.05), indicating significant differences among the SAFIRE Strength variations. Similarly, anatomical information data were analyzed using the Kruskal-Wallis statistical test, yielding a p-value of 0.000 (p < 0.05), confirming significant differences across the variations. The results of the study showed that there are significant differences in image quality and anatomical information among the five SAFIRE Strength variations. SAFIRE Strength 3 was identified as the most optimal for head CT Scan examinations in non-hemorrhagic stroke cases, as it produces images with minimal noise and higher detail, providing clearer anatomical information compared to the other SAFIRE Strength variations.